PCSK9-antibodies fail to block PCSK9-induced inflammation in macrophages and cannot recapitulate protective effects of PCSK9-deficiency in experimental myocardial infarction - Rauterberg, Simon; Härdtner, Carmen; Hein, Jennifer; Schrepf, Paola; Peyronnet, Remi; Koentges, Christoph; Vico, Tamara A.; Ehlert, Carolin; Dufner, Bianca; Lindner, Diana; von zur Mühlen, Constantin; Wolf, Dennis; et al. (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsProprotein convertase subtilisin/kexin type 9 (PCSK9) plays a crucial role in cholesterol homeostasis by regulating low-density lipoprotein (LDL) receptor levels. Despite its known effects on cholesterol metabolism, the role of PCSK9 in cardiac function, especially post-myocardial infarction (MI), remains unclear. This study investigates the impact of PCSK9 on heart function post-MI and evaluates the effects of PCSK9 inhibition via Alirocumab.MethodsWe used PCSK9 knockout (KO) mice and wildtype (WT) mice and in vivo treatment with Alirocumab to analyze cardiac function and survival post-MI induced by permanent ligation of the left anterior descending artery. PCSK9 and LDL receptor levels were measured using ELISA and qRT-PCR. Cardiac function was assessed via echocardiography and isolated working heart model experiments. Gene expression changes were evaluated using RNA sequencing, and inflammatory responses in bone marrow-derived macrophages (BMDMs) were analyzed in vitro.ResultsPCSK9 was expressed in murine heart tissue at levels comparable to the liver, despite minimal heart RNA expression. PCSK9 KO mice had lower plasma cholesterol levels and showed reduced cardiac functions in the working heart model compared to WT mice. Post-MI, PCSK9 KO mice demonstrated significantly improved survival and reduced ventricular rupture compared to WT mice. Alirocumab treatment, while effective in lowering plasma cholesterol, did not replicate the survival benefits seen in PCSK9 KO mice and even worsened cardiac function post-MI. In vitro, PCSK9 induced significant inflammatory responses in macrophages, which were not mitigated by Alirocumab.ConclusionPCSK9 accumulation in the heart post-MI contributes to adverse cardiac remodeling and inflammation. Genetic deletion of PCSK9 confers protection against post-infarct mortality, whereas pharmacological inhibition with Alirocumab fails to reproduce these benefits and may exacerbate cardiac dysfunction. These findings highlight the complex role of PCSK9 in cardiac pathology and caution against the assumption that PCSK9 inhibitors will necessarily yield cardiovascular benefits similar to genetic PCSK9 deficiency.